Care cascades for hypertension and diabetes: Cross-sectional evaluation of rural districts in Tanzania - Osetinsky, Brianna; Mhalu, Grace; Mtenga, Sally; Tediosi, Fabrizio (PLOS Medicine, 2022)
Background Noncommunicable diseases (NCDs), especially hypertension and diabetes, are rapidly rising in sub-Saharan Africa, necessitating health systems transformations. In Tanzania, current policies aim to improve control of hypertension and diabetes, but information is still needed to assess the gaps in treatment. Methods and findings We conducted a cross-sectional household survey of 784 adults in two districts in Tanzania from December 2020 to January 2021, capturing the cascade-of-care for hypertension and diabetes. The ages of the respondents ranged from 18 to 89 years. Of those screened positive for these conditions, we measured the proportion in each step of the cascades: awareness, care engagement, treatment, and control. We conducted multivariable logistic regression analyses for all four steps along the hypertension care cascade with the independent variables of social health protection schemes, and prior diagnosis of comorbid diabetes, and demographic information. In our sample, of the 771 who had their blood pressure measured, 41% (95% confidence interval (CI): 38% to 44%) were screened positive for hypertension, and of the 707 who had their blood sugar measured, 6% (95% CI: 4% to 8%) were screened positive for diabetes. Of those with hypertension, 43% (95% CI: 38% to 49%) had a prior diagnosis, 25% (95% CI: 21% to 31%) were engaged in care, 21% (95% CI: 3% to 25%) were on treatment, and 11% (95% CI: 8% to 15%) were controlled. Of the 42 respondents with diabetes, 80% (95% CI: 69% to 93%) had a prior diagnosis. The diabetes care cascade had much less drop-off, so 66% of those with diabetes (95% CI: 52% to 82%) were engaged in care and on treatment, and 48% (95% CI: 32% to 63%) had their diabetes controlled at the point of testing. Healthcare fee exemptions were independently associated with higher odds of being previously diagnosed (OR 5.81; 95% CI [1.98 to 17.10] p < 0.005), engaged in care (OR 4.71; 95% CI [1.59 to 13.90] p 0.005), and retained in treatment (OR 2.93; 95% CI [1.03 to 8.35] p < 0.05). Prior diagnosis of comorbid diabetes was highly associated with higher odds of being engaged in care for hypertension (OR 3.26; 95% CI [1.39 to 7.63] p < 0.005). The two primary limitations of this study were reliance on screening at a single time point only of people available at the village at the time of the sample and dependence on self-report for to inform the three cascade steps of prior diagnosis, healthcare visits for engagement in care, and treatment use. Conclusions The high burden of hypertension and low levels of control in our study underscores the importance of improving the awareness and treatment of hypertension. The differences in the care cascades for hypertension and diabetes demonstrates that chronic NCD treatment is possible in this setting, but efforts will be needed across the entire care cascade to improve hypertension control.